2017
DOI: 10.1111/pce.12926
|View full text |Cite
|
Sign up to set email alerts
|

Dual herbivore attack and herbivore density affect metabolic profiles of Brassica nigra leaves

Abstract: Plant responses to dual herbivore attack are increasingly studied, but effects on the metabolome have largely been restricted to volatile metabolites and defence-related non-volatile metabolites. However, plants subjected to stress, such as herbivory, undergo major changes in both primary and secondary metabolism. Using a naturally occurring system, we investigated metabolome-wide effects of single or dual herbivory on Brassica nigra plants by Brevicoryne brassicae aphids and Pieris brassicae caterpillars, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 70 publications
3
46
0
Order By: Relevance
“…Insect herbivory can modify plant physiology (Bolton, 2009) and alter metabolite concentrations in plant tissues (Griffiths et al, 1994;Hopkins et al, 1995;Ponzio et al, 2017) as well as nutrient uptake (Katayama et al, 2014;Aziz et al, 2016). It can also modify the release of organic matter by plant roots (rhizodeposition), a major driver of soil microbial communities (Singh et al, 2004;Paterson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Insect herbivory can modify plant physiology (Bolton, 2009) and alter metabolite concentrations in plant tissues (Griffiths et al, 1994;Hopkins et al, 1995;Ponzio et al, 2017) as well as nutrient uptake (Katayama et al, 2014;Aziz et al, 2016). It can also modify the release of organic matter by plant roots (rhizodeposition), a major driver of soil microbial communities (Singh et al, 2004;Paterson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When we manipulated single and dual-guild herbivory in our open-field experiments, we found that foliar concentrations of gluconapin were reduced by 30% in B. oleracea plants fed upon by both caterpillars and aphids rather than aphids alone (Fig. Indeed, recent greenhouse work in this system has shown that both the glucosinolate profile (Ponzio et al 2017), and the volatile chemical profile (Ponzio et al 2016) are distinct in single and dual infestations of aphids and caterpillars. A hydrolyzed volatile product of gluconapin, 3-butenyl isothiocyanate, is innately attractive to dominant aphid parasitoid species at our sites, D. rapae (Blande et al 2007, Pope et al 2008.…”
Section: Discussionmentioning
confidence: 81%
“…Still, while suggestive, our estimates of volatile precursors in a single species are only a proxy for examining volatile-mediated plant signaling in diverse communities. Indeed, recent greenhouse work in this system has shown that both the glucosinolate profile (Ponzio et al 2017), and the volatile chemical profile (Ponzio et al 2016) are distinct in single and dual infestations of aphids and caterpillars. Important next steps will be to test these mechanisms by combining field experiments that quantify parasitoid behavior with field-collection of volatile profiles of single and dual infested plants, across a variety of plant species and cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous colonization by nematodes and aphids on vegetative plants can thereby negatively or positively influence the effects that aphids have on seed production. Simultaneous herbivory can induce different plant responses as compared to induction by a single herbivore (Pierre, Jansen, et al, ; Ponzio, Papazian, Albrectsen, Dicke, & Gols, ). This can have consequences for plant‐mediated interactions (ChrĂ©tien et al, ; Soler et al, ; Stam, ChrĂ©tien, Dicke, & Poelman, ; Stam et al, ) and plant seed production (Stam et al, ).…”
Section: Discussionmentioning
confidence: 99%